Christopher Kaczor, A Defense of Dignity: Creating Life, Destroying Life, and Protecting the Rights of Conscience, Notre Dame: University of Notre Dame Press 2013, X+220 s. - Nowosad, Sławomir (Studia Nauk Teologicznych PAN, 2020)
Recenzja